Kepemilikan Manajerial sebagai Moderasi Pengaruh Kinerja Keuangan terhadap Financial Distress di Indonesia - Rahmansyah, Ahmad Iskandar; Hudzafidah, Khusnik; Bahri, Mohammad Saiful (RELASI : JURNAL EKONOMI, 2024)
One of the main problems influencing Indonesian corporate sustainability is financial distress. The moderating effect of managerial ownership on the impact of financial performance—more especially, liquidity ratios (cash ratio), solvency ratios (DER), and profitability ratios (ROI)—on financial distress is investigated in this paper. Data from 32 food-related companies listed on the Indonesia Stock Exchange (IDX) spanning 2020 to 2023 is used in the study. Analyzed using SmartPLS, which combines inner and outer model assessments to ascertain validity, dependability, and variable influence, Higher profitability and solvency ratios clearly help to lower financial stress; managerial ownership and liquidity have no direct bearing on this regard. Furthermore, managerial ownership indicates that higher managerial ownership reduces financial instability when solvency rises, so improving the relationship between solvency and financial distress. Managerial ownership does not, however, help to moderate the effects of liquidity and profitability on financial distress. These results underline the need of managerial ownership in improving corporate resilience against financial distress.